Everything is a poem : the best of J. Patrick Lewis - Lewis, J. Patrick (Creative Editions, 2014)
"A delightfully wide-ranging poetry collection taken from previously published and new works by American poet J. Patrick Lewis is illustrated by Italian artist Maria Cristina Pritelli"--